METODOLOGI PENELITIAN AGAMA MODEL DAVID S. POWER Critical Review Terhadap Buku Studies in Al-Qur’an and Hadith: The Formation of Islamic Law of Inheritance - Amin Nasrullah (AZKIYA, 2021)
The complexity of the problems in religious studies (Islam), which among others is due to its multi-interpretative nature, raises an urgent issue regarding what methodology is appropriate to be used in studying the Islamic problem. Also regarding which approach is appropriate to be able to understand and describe various religious phenomena and objects that become the study.The problem of methods and approaches is fundamental in any scientific study, but it is also not easy to determine them. Especially in the study (study / research) of religious issues. The difficulty in determining methods and approaches in religious studies, is not only in the matter of choosing the right method and approach to be applied to specific (specific) objects of study, but also because of the debate on the terrain of the methodology; which approach is more valid and valid to be used in religious studies. This article seeks to analyze and describe the methodology and approach used by David S. Power and is the result of a critical review of his research model in the book Studies in Al-Qur'an and Hadith: The Formation of the Islamic Law of Inheritance.Using literary, linguistic, lexicographic and historical approaches, a distinctive revisionist methodology complemented by rigorous historical studies; Historical literary analytical methods, as well as backward working procedures, David Power carried out a historical reconstruction of Islamic inheritance law. The results of his study (conclusions) provide something completely different from the legal tradition that has developed among Muslims so far. In the end, the authors concluded that the methodology and approach used by David Power was sufficient and could be used and developed in similar further studies. Although it also has some weaknesses.